2005
DOI: 10.1007/s11837-005-0059-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the hydrogen-induced cracking of titanium alloys in nuclear waste repository environments

Abstract: This paper reviews the current understanding of hydrogen-induced cracking (HIC) of Ti Grade 7 and other relevant titanium alloys within the context of the current waste package design for the repository environmental conditions anticipated within the Yucca Mountain repository.The review concentrates on corrosion processes possible in the aqueous environments expected within this site. A brief background discussion of the relevant properties of titanium alloys, the hydrogen absorption process, and the propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Inthefirststep,thegeneratedhydrogenmustdiffusethrough thetitaniumdioxidefilmandthenmustbeabsorbedatthe titanium-film interface. For absorption to proceed, the re-ductionofTi 4+ τοTi 3+ isnecessary.Thisoccursifaremarkable cathodicpolarizationoccurs,suchasinthepresenceofgalvaniccouplingwithzincoraluminum,orwhentitaniumisunder cathodicprotection.Whenthepotentialoftitaniumisbrought tovalueslowerthan-0.6VSaturatedCalomelElectrode(SCE) (Fig.7A),therateofhydrogenabsorptionincreases,reaching veryhighvaluesforpotentialsmorenegativethan-1.0VSCE (74).Abovethethresholdpotential,nohydrogenabsorption occurs. At sufficiently negative potential, hydrides are more stablethanthetitanium;inthiscondition,thepassivetitanium dioxideisasortofdiffusionbarriertohydrogen (Fig.7B).…”
Section: Hydrogen-induced Crackingmentioning
confidence: 99%
“…Inthefirststep,thegeneratedhydrogenmustdiffusethrough thetitaniumdioxidefilmandthenmustbeabsorbedatthe titanium-film interface. For absorption to proceed, the re-ductionofTi 4+ τοTi 3+ isnecessary.Thisoccursifaremarkable cathodicpolarizationoccurs,suchasinthepresenceofgalvaniccouplingwithzincoraluminum,orwhentitaniumisunder cathodicprotection.Whenthepotentialoftitaniumisbrought tovalueslowerthan-0.6VSaturatedCalomelElectrode(SCE) (Fig.7A),therateofhydrogenabsorptionincreases,reaching veryhighvaluesforpotentialsmorenegativethan-1.0VSCE (74).Abovethethresholdpotential,nohydrogenabsorption occurs. At sufficiently negative potential, hydrides are more stablethanthetitanium;inthiscondition,thepassivetitanium dioxideisasortofdiffusionbarriertohydrogen (Fig.7B).…”
Section: Hydrogen-induced Crackingmentioning
confidence: 99%
“…Studies about hydrogen induced cracking of Ti alloys were also conducted by Ikeda et al in Canada. The Canadian approach differs from the Japanese approach in that a critical absorbed hydrogen concentration (H C ) is used to define failure by hydrogen induced cracking rather than a critical hydride thickness [36]. Ikeda et al reported that the H C for titanium Gr 2, 12 and 16 was /g [37,38].…”
Section: Stainless Steels and Nickel Alloysmentioning
confidence: 99%
“…Ikeda et al reported that the H C for titanium Gr 2, 12 and 16 was /g [37,38]. It was also shown that for Ti Gr 2 and 12, the value of H C increased as the temperature increased [36].…”
Section: Stainless Steels and Nickel Alloysmentioning
confidence: 99%
“…Since TiO 2 is extremely insoluble, the corrosion reaction will be effectively limited to an oxide film growth reaction. 247 Titanium corrosion processes are often accompanied with hydrogen production, introducing the possibility of the absorption of hydrogen into the material. Crevice corrosion, once initiated, is supported by both the reduction of oxygen on passive surfaces external to the crevice and the reduction of protons (Ti + 4H + → Ti 4+ + 2H 2 ) inside the crevice, leading to the absorption of atomic hydrogen in sufficient quantities to produce extensive hydride formation.…”
Section: Reaction Of Titanium With Hydrogenmentioning
confidence: 99%
“…250,251 However, it was suggested that the work-hardening Ti-Ni alloy was less sensitive to hydrogen embrittlement compared with Ti-Ni superelastic alloy. 247 The reaction of Ti with hydrogen is not necessarily a useless phenomenon. The formation of titanium hydrides can provide an engineering advantage.…”
Section: Reaction Of Titanium With Hydrogenmentioning
confidence: 99%